Dynamics of total kinetic energy components in the atmospheric boundary layer from minisodar measurements - Krasnenko, Nikolay P. (Proceedings of SPIE)
The spatiotemporal dynamics of the total kinetic energy in the atmospheric boundary layer is analyzed in the present work, including the mean kinetic energy component and the ratio of the turbulent to mean kinetic energy components, retrieved by post-processing of long time series of vertical profiles of both average values and variances of the 3D wind vector measured with a minisodar. It can be used to analyze and to predict the dynamics of the wind effect on flying objects in the atmospheric boundary layer.